Implementation of Multicultural Education at the Mahasantri Campus of The Islamic Dirosat Institute of Al-Amien Prenduan - Andri Sutrisno; Ach. Nurholis Majid; Badrun Badrun (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2022)
The Islamic Boarding School Mahasantri Institute Dirosat Al-Amien Prenduan is part of the Indonesian state that instils multicultural values. Where the students come from various cultures, but they live in harmony with several types of educational programs that are implemented and implemented by the kyai and lecturers. It is very urgent in this research because all students live harmoniously without conflict because they accept all existing cultures with full support from educators. Meanwhile, the findings of this research are to understand the basic concepts of multicultural education, know about the implementation of multicultural education in Islamic boarding schools, and describe the supporting factors and obstacles to the implementation of multicultural education in these Islamic boarding schools. This research is qualitative research with the type of case study research; in collecting data, this research uses interviews, observation and documentation. Meanwhile, in analyzing this data, the researcher uses data reduction, presentation, and conclusion. So that this research gets a conclusion as follows: first, multicultural education is an effort created in society to respect each other between tribes and customs that each person has. Second, the implementation of this multicultural education is carried out in consulate parade activities, groups of students and recitation of Islamic religious books. In contrast, the supporters of this implementation include teaching and learning activities for 24 hours, and the obstacles are students' disobedience to regulations and lack of awareness of educational multicultural. values